1994
DOI: 10.1093/infdis/169.2.356
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Unilamellar Liposomal Amphotericin B in Treatment of Pulmonary Aspergillosis in Persistently Granulocytopenic Rabbits: The Potential Role of Bronchoalveolar D-Mannitol and Serum Galactomannan as Markers of Infection

Abstract: A model of primary pulmonary aspergillosis in rabbits was developed to reproduce the persistent levels of profound granulocytopenia and the histopathologic features of bronchopneumonia, vascular invasion, and hemorrhagic infarction encountered in humans. D-mannitol was detectable in bronchoalveolar lavage fluid by gas-liquid chromatography/mass spectroscopy, and galactomannan was measurable in serum by latex agglutination immunoassay. A pharmacokinetically distinctive unilamellar vesicle formulation of liposom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
120
0
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(131 citation statements)
references
References 40 publications
9
120
0
2
Order By: Relevance
“…to rabbits. Previous studies of experimental invasive pulmonary aspergillosis with rabbit models have demonstrated patterns of circulating galactomannan that are similar to those of humans for both detection and correlation with therapeutic response (1,4,8,10,16).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…to rabbits. Previous studies of experimental invasive pulmonary aspergillosis with rabbit models have demonstrated patterns of circulating galactomannan that are similar to those of humans for both detection and correlation with therapeutic response (1,4,8,10,16).…”
Section: Discussionmentioning
confidence: 91%
“…Healthy female New Zealand White rabbits (Hazleton, Research Products, Inc., Denver, Pa.) weighing 2.8 to 3.3 kg were used in an experiment (n ϭ 6). Rabbits were selected in these experiments because of the similarity between their patterns of expression of circulating galactomannan in experimental pulmonary aspergillosis and those found in humans with invasive aspergillosis (4,8,10,18). As in noninfected humans, rabbits have a normal mean GMI level well below the threshold of a positive value of 0.5.…”
Section: Methodsmentioning
confidence: 99%
“…Invasive pulmonary aspergillosis was established as described elsewhere (11). Briefly, Aspergillus fumigatus (A. fumigatus isolate NIH 4215, ATCC MYA-1163) obtained from a fatal case of IPA was used in all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…These curves were then used to define cutoff, sensitivity, and specificity values that optimized the test performance of each assay. Both methods were studied using a well-established persistently neutropenic rabbit model of IPA (11,28,42). We further investigated the impact of different antifungal modalities, including ravuconazole, micafungin, and deoxycholate amphotericin B, on the sensitivity and specificity of each assay.…”
mentioning
confidence: 99%
“…When the labeled probes align along the target in a sequence-specific manner, fluorescent energy is transferred from one dye to another to emit a signal in a different wavelength, hence the term FRET. We further validated the assay in a well-established animal model of IPA (6,17,24).…”
mentioning
confidence: 98%